Heat-stone massage for patients with chronic musculoskeletal pain: a protocol for multicenter randomized controlled trial - Li, Li; Xi, Yawei; Wang, Ying; Gao, Yinqiu; Lv, Xiaoying; Liu, Shu; Yang, Guangjing; Qian, Jingjing; Yang, Xiaofang; Ayad, Nardeen; Zhou, Jiayan; Sun, Ya Xuan; et al. (Frontiers in Medicine, 2023)
Introduction Chronic musculoskeletal pain bothers the quality of life for approximately 1.71 billion people worldwide. Although pharmacological therapies play an important role in controlling chronic pain, overuse of opioids, persistent or recurrent symptoms, and pain-related disability burden still need to be addressed. Heat-stone massage is using the heated stone to stimulate muscles and ligaments followed by massage for relax, which can potentially treat the chronic musculoskeletal pain. To determine the efficacy and safety of heat-stone massage for patients with chronic musculoskeletal pain is needed. Methods and analysis This multicenter, 2-arm, randomized, positive drug-controlled trial will include a total of 120 patients with chronic musculoskeletal pain. The intervention group will receive a 2 week heat-stone massage, 3 times per week, whereas the control group will receive the flurbiprofen plaster twice per day for 2 weeks. The primary end point is the change in Global Pain Scale from baseline to the end of the 2 week intervention. The secondary outcomes include the pain severity (Numerical Rating Scale), pain acceptance (Chronic Pain Acceptance Questionnaire), self-management (Health Education Impact Questionnaire), self-efficacy (Pain Self-Efficacy Questionnaire), anxiety and depression (Hospital Anxiety and Depression Scale), quality of life (Short Form-36). The intention-to-treat dataset will be used for analysis. Discussion The pain management remains the research topic that patients always pay close attention to. This will be the first randomized clinical trial to evaluate whether heat-stone massage, a non-pharmacological therapy, is effective in the chronic musculoskeletal pain management. The results will provide evidence for new option of daily practice. Clinical trial registration World Health Organization Chinese Clinical Trial Registry [ChiCTR2200065654; https://www.chictr.org.cn/showproj.html?proj=185403]; International Traditional Medicine Clinical Trial Registry [ITMCTR2022000104; http://itmctr.ccebtcm.org.cn/en-US/Home/ProjectView?pid=51776b6f-77b8-4811-9b5a-a0fec10f2cee].